2022
DOI: 10.1155/2022/3961233
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Processing under Microwaves

Abstract: Over the last decades, microwave heating has experienced a great development and reached various domains of application, especially in material processing. In the field of polymers, this unusual source of energy showed important advantages arising from the direct microwave/matter interaction. Indeed, microwave heating allows regio-, chemio-, and stereo-selectivity, faster chemical reactions, and higher yields even in solvent-free processes. Thus, this heating mode provides a good alternative to the conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…These ceramic components absorb microwave energy and subsequently transfer heat to the polymer matrix and the fibers through conduction. 41,42 This method results in more uniform processing of specimens that are thick with low thermal conductivity. 31 As a result, the microwaveconventional combined heating method offers more homogeneous heating throughout the composite material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ceramic components absorb microwave energy and subsequently transfer heat to the polymer matrix and the fibers through conduction. 41,42 This method results in more uniform processing of specimens that are thick with low thermal conductivity. 31 As a result, the microwaveconventional combined heating method offers more homogeneous heating throughout the composite material.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, microwave radiation also interacts with ceramic tiles or disks within the setup. These ceramic components absorb microwave energy and subsequently transfer heat to the polymer matrix and the fibers through conduction 41,42 . This method results in more uniform processing of specimens that are thick with low thermal conductivity 31 .…”
Section: Methodsmentioning
confidence: 99%
“…In summary, the research on FRP via the MAIL route is quite limited, requiring fundamental studies to clarify the interactions between MWs and reactants during the process of FRP. Therefore, the focus of further research studies should depend on the development of in situ observation instruments for FRP processes …”
Section: Synthesismentioning
confidence: 99%
“…Therefore, microwave absorbers can be used as susceptors to generate heat under microwave irradiation, indirectly heating the non-polar materials to enhance polymer devolatilization. [17] Concerning the characterization of volatiles in polymer particles, various detection methods have been used in the literature to obtain the solubility and diffusion coefficient of volatiles under different operating conditions. Iannello et al [18] studied the devolatilization of single polypropylene (PP) particles in a fluidized bed through X-ray imaging and a gas analyzer and found that high temperature and suitable fluidizing medium were conducive to the removal of volatiles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microwave absorbers can be used as susceptors to generate heat under microwave irradiation, indirectly heating the non‐polar materials to enhance polymer devolatilization. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%